Safety Culture, Moral Disengagement, and Accident Underreporting - Petitta, Laura (Journal of business ethics, 2017)
Moral disengagement (MD) is the process by which individuals mitigate the consequences of their own violations of moral standards. Although MD is understood to be co-determined by culture norms, no study has yet explored the extent to which MD applied to safety at work (JS-MD) fosters safety violations (e.g., accident underreporting), nor the role of organizational culture as a predictor of JS-MD. The current study seeks to address this gap in the literature by examining individual- (MD) and organizational-level (culture) factors that explain why employees fail to report workplace accidents. We tested a latent variable structural model positing organizational culture typologies (autocratic, bureaucratic, clan-patronage, technocratic, and cooperative) as predictors of JS-MD, which in turn is expected to mediate the relationship with accident underreporting. Using data from 1033 employees in 28 Italian organizations, findings suggest that bureaucratic safety culture was related to lower levels of JS-MD, whereas technocratic safety culture was related to greater JS-MD. In turn, JS-MD positively predicted employee accident underreporting and fully mediated the relationship between culture and underreporting. Theoretical and practical implications are discussed in light of the increasing focus on underreporting as well as the adverse individual and organizational consequences of failing to report workplace accidents.